Status of the Novosibirsk terahertz FEL - Bolotin, V.P.; Vinokurov, N.A.; Kayran, D.A.; Knyazev, B.A.; Kolobanov, E.I.; Kotenkov, V.V.; Kubarev, V.V.; Kulipanov, G.N.; Matveenko, A.N.; Medvedev, L.E.; Miginsky, S.V.; Mironenko, L.A.; et al. (Вопросы атомной науки и техники, 2006)
The first stage of Novosibirsk high-power free-electron laser (FEL) was commissioned in 2003. It is based on a normal conducting CW energy recovery linac. Now the FEL provides electromagnetic radiation in the wavelength range of 120…180 micrometers. An average power is 400 W. The minimum measured line width is 0.3%, which is close to the Fourier-transform limit. A user-beamline assembly is in progress, parts of the full-scale machine are manufactured. The latter will operate in the near IR region and provide higher average power В 2003 году в Новосибирске заработала первая очередь мощного лазера на свободных электронах (ЛСЭ). Машина построена на базе линака-рекуператора непрерывного действия. В настоящее время ЛСЭ работает в диапазоне длин волн 120…180 мкм, его средняя мощность достигает 400 Вт. Минимальная измеренная ши- рина полосы излучения составляет 0.3%, что близко к теоретическому минимуму. В настоящее время монтируются каналы разводки излучения для пользователей, части полномасштабной машины запущены в производство. Полномасштабная машина будет работать в ближнем ИК-диапазоне и обладать большей мощностью. В 2003 році в Новосибірську заробила перша черга потужного лазера на вільних електронах (ЛВЕ). Машина побудована на базі лінака-рекуператора безперервної дії. Зараз ЛВЕ працює в діапазоні довжин хвиль 120...180 мкм, його середня потужність досягає 400 Вт. Мінімальна виміряна ширина смуги випромінювання становить 0.3%, що близько до теоретичного мінімуму. Зараз монтуються канали розведення випромінювання для користувачів, частини повномасштабної машини запущені у виробництво. Повномасштабна машина буде працювати в ближньому ІЧ-діапазоні і мати більшу потужність.